Competency-based training in anaesthesiology: train the trainers first. A descriptive cross-sectional survey by the committee of the European Society of Anaesthesiology and Intensive Care (ESAIC) Teach the Teachers Masterclass - Vojislava Neskovic; Carmen Oliveira; Carmen Oliveira; Aeyal Raz; Lesley Bromley; Gordana Jovanovic (Frontiers in Medicine)
IntroductionThe level of competence in teaching among trainers expected to deliver training according to the European Training Requirement in anaesthesiology is unknown. The aim of this descriptive cross-sectional survey, performed from 1 September 2021 until 31 October 2021, and promoted by the European Society of Anaesthesiology and Intensive Care (ESAIC) was to establish the current level of knowledge and faculty development among European countries regarding competency-based education and training (CBMET) in anesthesia and intensive care.ResultsA total of 711 responses of anaesthesiologists working in 46 European countries were analyzed. The great majority (530/74.64%) had more than 10 years of experience in anesthesia, were experienced specialists, or held more senior positions (645/90.97%), worked in academic hospitals (451/63.5%), and claimed to be involved in teaching residents (561/79.01%). Most respondents declared either not sure or no knowledge (115/546; 21.06% and 232/546; 42.49%) about European training requirements in anaesthesiology. One-third claim to know about CBMET. Formal training in teaching has 21% of respondents. Lack of time (369/506; 72.92%) and overload with work (351/506; 69.36%) are reported as the most important obstacles in teaching residents. A disparity in the answers is present between, but within the countries too.ConclusionsThe results of the presented survey reveal that even among experienced anesthesia professionals dedicated to medical education there is still a lack of knowledge on CBMET as well as systemic support for faculty development in European countries. The differences within and between European countries regarding the perception of CBMET. Dedication to faculty development is necessary to improve European anesthesia and intensive care education.